Gröna narrativ och segregerande bostadspolitik: En undersökning av problemrepresentationer i stadsplaneringsdokument rörande Köpenhamns hållbara utveckling - Johansson,Ebbalisa (2025)
The study critically examines the image of Copenhagen as a “sustainable”, “inclusive” and “livable” city, specifically in relation to the political initiative known as the “ghetto law” – a social mixing policy introduced in 2018 aimed at creating a “balanced” population, combating crime, and preventing the formation of “parallel societies”. The study operates under the premise that governance is shaped through problematizations, and it identifies three key problematizations related to Copenhagen’s sustainable and inclusive development using the “WPR” method of analysis. By analyzing policies and problematizations within Danish urban development documents, the study uncovers underlying neoliberal rationalities and interests, offering a critical lens for interpretation. The study further explores how green narratives can obscure uneven development and gentrification processes, and it challenges the fundamental objectives of “urban renewal” initiatives within the neoliberal city.
Keywords: green gentrification; greening; gentrification; social housing; social mixing; segregation; “ghetto”; neo-liberalism; Copenhagen; “WPR